DETERMINANTS OF CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE IN THE MINING COMPANIES - Ari Kharisma (Asosiasi Dosen Muda Indonesia, 2026)
This study examines the influence of firm size, profitability, and leverage on Corporate Social Responsibility (CSR) disclosure among mining companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. Employing a quantitative research design with a descriptive approach, the study utilizes secondary data obtained from annual reports and sustainability reports. The sample consists of 13 mining companies selected from a population of 59 companies through purposive sampling. Data were analyzed using multiple linear regression to assess both partial and simultaneous effects of the independent variables on CSR disclosure. The findings reveal that firm size has a significant positive effect on CSR disclosure, indicating that larger companies tend to disclose more comprehensive CSR information. In contrast, profitability and leverage do not exhibit a significant influence on CSR disclosure when assessed individually. Nevertheless, the simultaneous test demonstrates that firm size, profitability, and leverage collectively have a significant effect on CSR disclosure. These results suggest that while firm size serves as a key determinant of CSR disclosure practices in the mining sector, the combined interaction of financial and organizational characteristics also contributes to variations in CSR reporting.